Microsoft Excel 2021/365 : beginner to advanced. (Packt Publishing, 2022)
Microsoft has released its latest stand-alone Excel version, which opens up many of the features and functionalities that are available only in Excel 365 through a subscription. In the first section, we study some basics about how to use Excel 2021 and become familiar with what's new in it. We will first navigate the Excel 2021 interface and create our first Excel spreadsheet. You will learn some useful keyboard shortcuts to increase productivity, learn how to effectively apply formatting to cells and use conditional formatting, learn how to use basic and intermediate Excel formulas and functions, and more. Then, in the second section, you will learn how to create intermediate-level formulas, prepare data for analysis using PivotTables and Pivot Charts, make use of WhatIf analysis tools, learn how to use validation rules to control data input, and explore the fundamentals of spreadsheet design. In the final section, we will build on the skills learned in the beginner and intermediate sections and fast-track our way to being an Excel power user. This section covers the latest updates from Microsoft, including the LET and LAMBDA functions, which allow us to create our own variables and even Excel functions. By the end of this course, you will be able to use Excel skills confidently. What You Will Learn Become familiar with what's new in Excel 2021 Use Excel lists and master sorting and filtering Represent data visually with Pivot Charts Use WhatIf analysis tools to see how changing inputs affect outcomes Analyze data with advanced PivotTable and PivotChart hacks Import and clean data using Power Query Audience If you are an absolute beginner who has never used Excel before, this course can give you a great foundation. You might have some basic Excel skills and want to improve your proficiency, or you are using an older version of Excel and want to check out what's new. Well, this course can help you get the ball rolling. About The Author Simon Sez IT: Simon Sez IT has offered technical courses since 2008 for individuals, small businesses, and Fortune 500 companies with thousands of employees who can benefit from the easy-to-learn and hands-on software training. It offers over 8000 video tutorials on a range of software programs. Simon Sez IT ensures stress-free eLearning and enhanced employee productivity--whether you implement new software or a technological upgrade in your work environment. With over 600,000 students from 180 countries, Simon Sez IT is the preferred online learning choice for individuals and businesses worldwide.